UJI EFEKTIVITAS CUKA APEL TERHADAP PERTUMBUHAN Malassezia furfur SECARA IN VITRO DENGAN METODE DIFUSI PERFORASI - Bella Siti Syafina (2019)
Malassezia furfur is part of flora normal that can become and pathogenic if an imbalance found in the host cell . Apple cider vinegar is widely discussed due to its health-promoting properties and empiric data shows that apple cider vinegar has antifungal activity. This study was aimed to determine the antifungal activity of apple cider vinegar and the minimum inhibition concentration along with the effective concentration of apple cider vinegar. A qualitative test method was used for phytochemical screening. This study used five different concentrations which is 12.5%, 25%, 50%, 75% and 100%. Ketoconazole 200 mg was used as a positive control since it is clinically proven to inhibit fungal growth, and aquades was used as a negative control. Antifungal activity test was performed using the perforation diffusion method. Result Phytochemical screening contained in apple cider vinegar: acetic acid, flavonoids, alkaloids, and glycosides. Apple cider vinegar has antifungal activity against the growth of Malassezia furfur with a minimum inhibitory concentration of 25% and an effective inhibitory potential at a concentration of 75%.